PENGALAMAN ADAPTASI KARYAWAN TERHADAP IMPLEMENTASI ARTIFICIAL INTELLIGENCE DALAM PROSES KERJA: STUDI INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Yanurianto Yanurianto; Lilis Suryani; San Ridwan Maulana (LAP4B, 2026)
This research aims to explore in depth the life experiences of employees in the process of adapting to the implementation of artificial intelligence (AI) in the workplace. The phenomenon of work digitalization accelerated by the dynamics of industry 4.0 has prompted organizations to integrate AI systems into their daily operational workflows, but individual employee responses to these changes are still very poorly explored qualitatively. This study uses the Interpretative Phenomenological Analysis (IPA) approach developed by Smith, Flowers, and Larkin as the main methodological framework to understand the subjective meaning of the adaptation experience. Data collection was conducted through in-depth semi-structured interviews with eight purposively selected participants based on criteria of direct involvement with AI systems in their work for a minimum of six months. The data analysis yielded four superordinate themes, namely: (1) the shock of professional identity, (2) the negotiation of new competencies, (3) ambivalence towards work autonomy, and (4) the reconstruction of the meaning of work post-AI. The findings of the study indicate that adaptation to AI is not just a technical process, but rather a complex psychological journey that involves cognitive, emotional, and social dimensions simultaneously. This research makes a theoretical contribution to the development of an AI-based work adaptation model as well as practical implications for human resource management in designing a more humanistic change assistance program centered on the subjective experience of employees.